Uso de Métodos Monte Carlo na Modelagem de Fontes Radioativas Naturais - Gutemberg Luiz Sales Claudino; José Vieira; Viriato Leal Neto; Fernando Lima; José Santos (Brazilian Journal of Radiation Sciences)
Exist, in Brazil and in the world, different places with high levels of ambient radiation, mainly due to the presence of primordial radionuclides, exposing populations to risks that can not be neglected. To evaluate the distribution of the absorbed dose to organs and tissues of a human body, the Group of Numerical Dosimetry (GDN) utilizes Computational Models Exhibition (MCES), that use a voxel phantom and the Monte Carlo code EGSnrc to simulate the transport of radiation, its interaction with the atoms of the medium and evaluate the energy deposited in regions of interest. Essentially, if tried improve the way the photons are sampled in the plan, taking in account the probability density function (PDF) that describes the problem, the runtime simulation and dosimetric results. This article, was simulated a circular region of soil with the phantom center and limited by a maximum radius (rmax), from where, because of concentration of natural radioactive elements, photons can emerge with diverse energies and radial distribution similar to that modeled by GDN. The objective is to investigate the influence of rmax in the dosimetric results. To perform the simulations was adapted MCE MSTA, composed by phantom MASH (Male Adult meSH) in orthostatic position coupled to EGSnrc, with the algorithm of FDP NT allowing execution for different values of rmax. From  rmax = 2000 cm, It is found that the dosimetric values do not vary significantly, no offsetting the increased computational time spent to simulate higher values of rmax.